A Puff of Smoke, a Hole in the Pocket, Fissure in the Lungs and Profit in Millions. Issue 2 (September 2019) - Anand, Manoj; Singh, Jagandeep
The idea that business is a medium to deliver goods and services in lieu of profits is outmoded. The triple bottom line (profit, people and planet) approach is no longer a buzzword. It is a reality and a pressing need. There is no denying the fact that 'corporate India' too has embraced the philosophy of 'doing well by doing good'. All appears hunky-dory when cash rich and highly profitable firms are hailed for being socially responsible organizations. However, at times, the situation may be ironical. An organization, seen as an epitome of altruism, is engaged in the manufacturing of a legal, albeit potentially harmful product. Any organization in the cigarette industry would fit this bill to perfection. Business schools globally have revisited their course curriculum with increased focus on sustainability. Varun Chopra, on his day one of the MBA induction programme, has been confronted with a fundamental question: why do organizations exist? The answer to the complex question has to be examined through the lens of different stakeholders. Is there a simple answer as the interests of different stakeholders may be divergent? Scouting for an answer to this question in the cigarette industry draws attention to the need to juxtapose economic, social and environmental objectives.